Drug in Adhesive Transdermal Formulation of Valsartan and Nifedipine: Pharmacokinetics and Pharmacodynamics in Rats - Sood, Jatin; Sapra, Bharti; Tiwary, Ashok K. (Current Drug Therapy, 2019)
Background: The increasing complications associated with hypertension often require a combination of two or more drugs acting through different routes to counter the elevated blood pressure. Objective: The present investigation envisaged at preparing and evaluating a transdermal formulation containing gelled microemulsion drug in adhesive (DIA) patch for simultaneous systemic delivery of valsartan and nifedipine aimed at effective management of hypertension. Methods: An optimized microemulsion was prepared by using Captex® 500 (7.34% w/w), Capmul® MCM (4.24% w/w), Acrysol EL 135 (24.43% w/w), Transcutol P® (5% w/w) and water (58.9% w/w). Gelling was contributed by polyvinylpyrrolidone K 90F and polyethyleneimine where the latter also conferred skin adhesion properties to the patch. DIA patches were evaluated for in vitro drug release as well as in vivo pharmacokinetics and pharmacodynamics in rats. Results: In vitro permeation of nifedipine or valsartan from the selected DIA patch was 10.67-fold and 1.25-fold higher as compared to their aqueous dispersions. The relative bioavailability of nifedipine was 1.34 and that of valsartan was 2.18 from this DIA patch with respect to the oral administration of their aqueous suspension. Conclusion: Transdermal delivery of either drug alone was not effective in reducing methyl prednisolone acetate-induced hypertension, whereas, simultaneous transdermal delivery of both drugs from DIA patch effectively maintained systolic blood pressure at a normal level in these rats for 20 h.
Keywords: microemulsion